THE RELATIONSHIP OF MOTHER'S EDUCATION LEVEL, ACCURACY OF SUPPLEMENTARY FEEDING (MP ASI) WITH NUTRITIONAL STATUS OF TOLLS AGED 6-24 MONTHS - Umi Hani'ah; ‪Paulinus Deny Krisnanto; Januar Rizqi (P3M Universitas 'Aisyiyah Surakarta, 2022)
The provision of excellent or appropriate MP-ASI will significantly affect the growth and development of children and children's intelligence. Giving MP-ASI that is not appropriate will impact problems in the nutritional status of children such as undernutrition status and overnutrition status to obesity. The introduction and provision of MP-ASI should be made gradually from liquid, semi-solid, and solid foods. This study aimed to determine the relationship between maternal education level and the accuracy of complementary feeding (MP ASI) with the nutritional status of children under five. This research is a quantitative analytical observation with a cross-sectional design. The research sample was 74 children aged 6-24 months, obtained using accidental sampling technique, data analysis using the Chi-Square test, and Fisher's alternative test. The results showed that the relationship between a mother's education level and the nutritional status of children under five was obtained with a p-value of 0.111 (p-value <0.05). The relationship between the accuracy of giving MP-ASI with the nutritional status of children under five obtained a p-value of 0.038 (p-values <0.05). This study concludes that there is no relationship between the mother's level of education with the accuracy of giving complementary feeding and the nutritional status of children under five. There is a relationship between the accuracy of giving MP-ASI with the nutritional status of toddlers.